Local Issue, National Media, and Global Implication: Media Construction of Reality about Qanun of Aceh Polemic - Yuhdi Fahrimal; M. Isnaini; Apriliyanti Pratiwi; Hamida Syari Harahap; Wien Kuntarie (CoverAge: Journal of Strategic Communication, 2018)
Polemic endorsement Qanun Number 3 of 2013 on Flag and the Symbol of Aceh has reached the stage of open conflict between Indonesia Government and Aceh Government. This conflict is constructed by the media using various framing devices. The consequence of media framing is the escalation of public opinion towards one-way interpretation of the media. In building a peaceful climate, the media has a very important role. The role of the media is not merely a transmitter of information and control of social reality, but the media plays a role in improving and providing citizens with a better understanding of the importance of sustainable peace for successful development.